Effect of Hyperbaric Oxygen Therapy on Polarization Phenotype of Rat Microglia After Traumatic Brain Injury - Liang, Fang; Kang, Nan; Li, Pinpin; Liu, Xuehua; Li, Ge; Yang, Jing (Frontiers in Neurology, 2021)
Background: The neurological defect caused by secondary damage following traumatic brain injury (TBI) is considered critical for the management of TBI. Microglia (MG) are a resident brain macrophage that could differentiate into M1 type or M2 type in response to injury and repair. It is known that the MG transition from M1 phenotype to anti-inflammatory M2 phenotype might reduce secondary injury of TBI. So, a TBI animal model was established and we compared biomarkers of M1 and M2MG between the controls and experimental animals receiving hyperbaric oxygen therapy (HBOT). This study aimed to explore whether HBOT was an effective method to improve neural functional recovery via promoting the polarization of MG into M2 after TBI. Methods: The rats were randomly divided into four groups: SH (Sham-operated), SH + HBO (hyperbaric oxygen), TBI, and TBI + HBO. Each group included 42 rats, and each of these were divided into the following groups: 1, 6, 12, 24, 72 h, 7, and 14 days. The expression of M1 biomarker inducible nitric oxide synthase (iNOS), M2 biomarker arginase 1 (Arg1), associated cytokine tumor necrosis factor-α (TNF-α), and transforming growth factor-β1 (TGF-β1) was evaluated after the observation time. Results: TBI significantly increased the expression levels of M1 marker iNOS and M2 markers Arg1 at different time points. The increased expression of iNOS was suppressed, while the expression level of Arg1 was enhanced by HBOT. Moreover, HBOT suppressed the pro-inflammatory TNF-α secreted by M1, and promoting the anti-inflammatory TGF-1β. Conclusions: In the present study, HBOT showed the effects on shift of M1 toward M2 phenotype with increased expression of M2 biomarkers and decreased expression of M1 biomarkers in the early stage after TBI.